Die regionale Erfassung sekundärer Beschäftigungswirkungen.: Das Beispiel der Ford AG in Köln - Boesler, Klaus-Achim; Bott, Annelie (ERDKUNDE, 1991)
It is often pointed out that a great variety of economic and political activities cause so-called secondary employment effects in enterprises and households originally not affected through the increasing complexity of trade relations. Due to the lack of an adequate method to measure these effects a lot of publications dealing with this subject demand a quantitative data-base. In addition it is being criticized that the immediate and mediate spatial employment effects which can be produced on a regional and global scale are neglected. The purpose of this paper will be to demonstrate that this problem can at least be solved in part: the present investigation regards the following most important secondary employment effects: the effects of procurement linkages and wage payments of a single enterprise or as well of a whole sector of the economy in a certain region. First of all , the above mentioned data have specifically to be collected for the company under consideration. This information is to be summed up according to the sectoral und spatial distribution of the suppliers and employees. Then they can be combined with an amplified open input-output-model. For this purpose various vectors are to be inserted in STÄGLIN/PIRSCHNER'S amplified open input-output-model, which is based upon the investigations of LEONTIEF. In conjunction with an appropriate arrangement of the different model-steps, this procedure enables not only an entirely sectoral but also very extensively spatial allocation of the secondary employment effects. To set an example, this method is demonstrated by means of Ford AG in Cologne. Merely through the purchase from suppliers in North Rhine-Westphalia and through the wage payments to employees living in Cologne and its hinterland, the Ford AG causes extensive nationwide employment effects. Yet not only the classical car-supplying industries profit by these linkages but also branches not producing automotive components. The spatial analysis mainly focuses on Cologne, the plant's location, and its hinterland. Here the employment effects prevailing are based upon the direct procurement linkages of the FORD AG. While in the hinterland every 10th job in the spare part-industry is occupied by demands from the FORD AG, this company obtains from the city of Cologne mainly service- and commercial deliveries. Considering the increasing trend to JIT-supply the analyses of supply-induced secondary employment effects will gain in importance particularly at the location of the plant under consideration.